(untitled) (Medico Legal Update, 2020)
Background: Health services provided to the community were often overlapped among health care professionals. Poor communication may affect the quality of patient care and potentially increase the number of medical errors. Objective: The study aims to analyze the most determinant factors associated with the implementation of Interprofessional Collaboration (IPC) at Labuang Baji General Hospital. Method: The study used a cross-sectional design for data collection method. A questionnaire was administered to 291 respondents. The data analysis was performed using a computer program and statistical analysis, namely Univariate analysis distribution (of frequency) and logistic regression. Results: The results reveal that the determinant factors affecting the implementation of IPC are Communication (P = 0.000), Trust and Respect (P = 0.017), Administrative Support (P = 0.000), Culture (P = 0.000), Law and Regulations (P = 0.001), and Finance (P = 0.000). Conclusion: An effective communication with other healthcare teams in the implementation of IPC leads to effective and safe healthcare services at Labuang Baji General Hospital, Makassar. Based on this reason, a policy is needed to improve the implementation of IPC in Labuang Baji General Hospital.